2017
DOI: 10.36456/stigma.vol10.no1.a635
|View full text |Cite
|
Sign up to set email alerts
|

EFEKTIVITAS EKSTRAK DAUN MENGKUDU (Morinda citrifolia L.) DAN DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) TERHADAP ZONA HAMBAT PERTUMBUHAN Staphylococcus aureus

Abstract: Has conducted research on the effectiveness of various concentrations of noni leaf extract (Morinda citrifolia L.) And red betel leaf (Piper crocatum Ruiz & Pav) the growth inhibition zone of staphylococcus aureus. Inhibition test using paper disc diffusion method. Paper discs soaked in noni leaf extract and red betel leaf for 30 minutes and placed on media that has been spread bacteria staphylococcus aureus and then incubated for 24 hours. The results showed that noni leaf extract and red betel leaves wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The phytochemical properties of M. citrifolia fruit extract contained flavonoids (such as flavones, flavonols, anthocyanidins, flavanols, flavanones, flavanonols, aurones, furan chromones, isoflavones, isoflavonones, biflavones, xanthones, chaocones, and dihydrochalcones), tannins, and steroids (such as stigma sterol, daucosterol, and β-sitosterol), similar to previous reports (Nagalingam et al 2012;Afiff and Amilah 2017;Youn and Chang 2017;Sogandi and Nilasari 2019;Yee 2019;Ayunda et al 2020). This study showed that the major components of M. citrifolia fruit extract were 2-fluorobenzoic acid, eucalyptol, 2chloroaniline-5-sulfonic acid, hexadecamethyl octasiloxane, and tetrapropyl stannane.…”
Section: Discussionsupporting
confidence: 89%
“…The phytochemical properties of M. citrifolia fruit extract contained flavonoids (such as flavones, flavonols, anthocyanidins, flavanols, flavanones, flavanonols, aurones, furan chromones, isoflavones, isoflavonones, biflavones, xanthones, chaocones, and dihydrochalcones), tannins, and steroids (such as stigma sterol, daucosterol, and β-sitosterol), similar to previous reports (Nagalingam et al 2012;Afiff and Amilah 2017;Youn and Chang 2017;Sogandi and Nilasari 2019;Yee 2019;Ayunda et al 2020). This study showed that the major components of M. citrifolia fruit extract were 2-fluorobenzoic acid, eucalyptol, 2chloroaniline-5-sulfonic acid, hexadecamethyl octasiloxane, and tetrapropyl stannane.…”
Section: Discussionsupporting
confidence: 89%
“…Tumbuhan yang dapat digunakan sebagai antibakteri salah satunya adalah daun mengkudu. Mengkudu memiliki kandungan kimia seperti saponin, alkaloid, tanin, flavonoid, triterpenoid, antrakuinon, karoten, zat besi, zat kapur, senyawa moridin, aligerin-d-methyleter, xeronin, soranyideal, proxeronin, antioksidan, vitamin C, vitamin aA, askorbin, moridon, protein, lemak, kalori, niamin, karbohidrat, riboflavin, thiamin, mineral (kalsium, kalium, zat besi, natrium) [6,7].…”
Section: Pendahuluanunclassified
“…The activity of these compounds can damage the cell membrane or cell wall of bacteria. These compounds are mostly contained in the red leaves, but under certain conditions red betel leaves can change color (Afiff & Amilah, 2017). Leaves that are initially red at the bottom will change color to green and the silvery pattern will disappear (Rachmawaty et al, 2018) Staphylococcus epidermidis is a normal flora on the skin and is not pathogenic, but if there is a change in skin condition, the bacteria can become invasive (Lutpiatina, 2017).…”
Section: Introductionmentioning
confidence: 99%